2020
DOI: 10.1111/ssqu.12776
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Cultural Retention–Delinquency Relationship Using Differential Support and Coercion Theory: A Study of Native‐Born and Immigrant Latino Youth

Abstract: Objective Although immigrants tend to have lower involvement in delinquency, increasing levels of acculturation to American society may lead to higher levels of delinquency. Conversely, cultural retention typically reduces such behavior. To explain these findings, this study employs differential coercion and support theory to predict that cultural retention is inversely associated with delinquency through associations with greater social support and less coercion. Method Using a large, national‐level sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
0
8
1
Order By: Relevance
“…Furthermore, enculturation was somewhat surprisingly nonsignificant. Prior research has found that enculturation decreases criminal behavior (Zavala et al, 2020). However, this was not the case here.…”
Section: Discussioncontrasting
confidence: 71%
“…Furthermore, enculturation was somewhat surprisingly nonsignificant. Prior research has found that enculturation decreases criminal behavior (Zavala et al, 2020). However, this was not the case here.…”
Section: Discussioncontrasting
confidence: 71%
“…Another important source of social support may come in the form of enculturation, or the retention of immigrant culture. Defined as the process of adaptation to one’s ethnic culture (Cano & Castillo, 2010), research on enculturation shows associations with a reduced likelihood of delinquency among youth (Zavala et al, 2020). This may be because enculturation represents a source of social support, whereby strong connections are maintained to the traditional cultural values and norms of the country of origin, often including language usage.…”
Section: A Latinx Dcssmentioning
confidence: 99%
“…First, this study answers the call made by progressive scholars to establish and test theories that take into account how the particular life experiences of marginalized individuals influence their likelihood of engaging in criminal behavior (Unnever et al, 2020). While the link between acculturation and crime is well documented in the literature, exactly why this is the case is starting to become clearer among Latinx youth (Zavala et al, 2020), but not, as of yet, on Latinx adults. Second, solely focusing on Agnew’s (2006) general strain theory and its reformulation into Latinx general strain theory may prevent other correlates outside of strain from being discovered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown a consistent relationship between acculturation and crime, showing that a greater level of acculturation among Latinx is asscoaited with an increased risk for future criminal engagement (Bersani, 2014; Jennings et al, 2013). Existing scholarship has also linked acculturation to alcohol and drug use (Gil et al, 2000), criminal and delinquent behavior (Zavala et al, 2020), and physical aggression (Maldonado-Molina et al, 2010). For example, Perez et al (2008) examined how ethnic-specific strains – including measures of acculturation (e.g., nativity and language proficiency) – unique to Latinx adolescents were related to violent delinquency.…”
Section: Latinx General Strain Theory and Acculturationmentioning
confidence: 99%